KELUARGA TIDAK HARMONIS DALAM KARYA LUKIS - RIYAN PATRIO, Drs. Erfahmi, M.Sn., Drs. Efrizal, M.Pd. (Serupa The Journal of Art Education, 2019)
The final work aims to visualize a non-harmonious family, so that people know the conditions and conditions of children when harmony is not present in a family at this time. At this time many children from families who are not harmonious actually want a harmonious family.Ten works that were raised told about the condition and impact of Non-Harmonious Families in Indonesia. Some things start with the arguments between the parents and the divorce that has a negative impact that must be avoided in family conflicts. The effects of divorce and non-harmonious families are still many that we encounter in people's lives and have a strong impact on the child, as has been manifested in contemporary painting about the non-harmonious visualization of the family in the community.Kata kunci: Keluarga Tidak Harmonis, Seni Lukis